Study In Silico Senyawa Asam Asiatik dan Turunannya Sebagai Anti Katarak - Fadila, Firlia Nur; Sanjaya, I Gusti Made (Al-Kimia, 2021)
This study aims to examine asiatic acid from Barringtonia asiatica seed extract as an anti-cataract. The presence of asiatic acid in the extract was confirmed using LCMS. The study was conducted using the HKSA method and it is independent of the molecular docking method. Molecular modeling was carried out using the Avogadro program. Descriptors computation using NWChem (DFT method, 6-311G base set), Swiss ADME, Molinspiration, and ADMET. Molecular tethering and visualization using Autodock Tools 1.5.6. and Discovery Studio 2019 Client. The best compounds that fight against cataracts are 9- (methoxymethyl)-1,2,6a, 6b, 9,12a-hexamethyl-10,11-dioxo-1,2,3,4,4a,5,6,6a, 6b,7,8,8a, 9,10,11,12,12a, 12b,13,14b-icosahydropicene-4a carboxylic acid. The equation: Log P = 25.593 + (- 0.136) * PSA + (-1.694) * Surface area + (-0.015) * Volume + (1.368) * molar refraction + (0.129) * LUMO + (- 7.007) * HOMO + (- 0.117) ) * E DFT + (-0.037) * E Hydration + (- 0.262) * Polarization This molecule was confirmed to be anti-cataract based on the molecular docking against the 4JGF protein target which produced binding energy and inhibition constants of -8.78 and 0.3368 uM.